Pengawasan Kebijakan Pemungutan Cukai Etil Alkohol Dan Minuman Mengandung Etil Alkohol Di Kantor Direktorat Jenderal Bea Dan Cukai Jakarta Timur - Anisa Nurul Wahyuni; Selvi Selvi (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this research is to analyze the supervision of ethyl alcohol and beverages containing ethyl alcohol excise collection policy and obstacles in supervising the policy. The research used a qualitative research method. Primary data was obtained through direct observation on the field and interview while secondary data was obtained through documents related to the supervision of ethyl alcohol and beverages containing ethyl alcohol excise collection policy. The findings of research conducted by the researcher at East Jakarta Directorate General of Customs and Excise (DJBC) show that indirect supervision is not sufficient so direct supervision is required to perform. The obstacles faced are limited human resources leading to inefficient internal supervision. Supervision without awareness and personal capabilities in an institution will only cause frauds and issues. The suggestion from the researcher is that DJBC has to improve socialization to excisable goods employers so they will not attempt to evade DJBC. For better performance in the future, all related parties either DJBC or public should cooperate to perform supervision.